Social support and economic conditions among older migrants in India: do distance, duration, and streams of migration play a role in later life? - Vasim Ahamad; Ram Babu Bhagat; Manisha; Sanjay Kumar Pal (BMC, 2024)
Abstract Background Being older and having a migrant feature might cause a double risk of vulnerability in poor economic, social support, and health status at the place of destination. This study examines the association of migration on the social support and economic condition of older persons in India. Methods Longitudinal Ageing Study in India (LASI) wave-I (2017-2018) data with total samples of 66,156 older adults aged 45 + with 30,869 and 35,287 male and female samples, respectively, used in this study. Descriptive and bivariate analyses have been performed to examine the pattern of older migrants, and multinomial logistic regression analysis has been used to establish the associations between migration, social support, and economic condition. Results Over half (57.5%) of the population aged 45 + in India had migrant characteristics; 80% migrated before 25 years. Of all migrants, about 90% migrated within one state (Intrastate), and 9% migrated to another (Interstate). The association between social support and migration by distance and the adjusted result showed that immigrants were less likely to have medium [RRR = 0.56 (CI; 0.46-0.68)] and high [RRR = 0.39 (CI; 0.30-0.50)] social support. The interstate migrants were also less likely to have high [RRR = 0.90 (CI; 0.83-0.98)] social support. The migrants with 0-9 years of duration were less likely to have high social support, and the urban to rural stream migrants were more likely to have high social support. The association between economic status and migration by distance and the adjusted result showed that more affluent immigrants were likelier to have [RRR = 1.41 (CI; 1.14-1.73)] better economic conditions than affluent non-migrants. Migrants with 0-9-year duration and urban to rural stream were found to be likelier to have better economic conditions. Conclusions The findings of this study suggest that distance, duration, and migration stream have a significant association with social support and economic conditions in later life. In exploring migration's effect on social and economic status, policymakers should prioritize migrants in their agenda to maintain socio-economic and social support for older persons in India to achieve the sustainable goal of active and healthy ageing.